The The Relationship Between Age, Employment Status, Gender, Linezolid Use, and Hiv Status on The Survival Duration of Short-Term Treated MDR-TB Patients - Azmiardi, Akhmad; Zakki Saefurrohim, Muhamad; Henda Ardiani, Intan (Panakeia Journal of Epidemiology, 2024)
This study evaluated the association of demographic and clinical factors with the survival of drug-resistant TB (MDR-TB) patients undergoing short-term treatment. Using a retrospective cohort design, data were collected from the medical records of 38 MDR-TB patients who received short-term therapy in 2021-2023 at a Central Java hospital. The variables analyzed included age, employment status, gender, Linezolid (Lzd) use, HIV status, and treatment initiation time. The results of logistic regression analysis showed that employment status and gender significantly influenced survival. Patients who were employed had a higher chance of survival than patients who were not employed (Exp(B) = 38.884; p = 0.011). Female patients showed better outcomes than males (Exp(B) = 0.031; p = 0.011). Age showed a weak association with survival, with older age tending to decrease survival although not significantly (p = 0.052). HIV status and timing of early treatment initiation also showed potential to affect survival, but were not significant (p > 0.05). Lzd use showed no significant effect on survival (p = 0.441). This study concludes that occupation and gender are important predictors of survival in MDR-TB patients, while other factors require further research.